Job polarisation: Capturing the effects of work organisation - Lopes, H.; Calapez, T. (Economic and Labour Relations Review, 2021)
This article critically challenges the findings and assumptions of mainstream job polarisation literature. Based on the European Working Conditions Survey data and on the Job Demand-Control model, which allows for capturing the organisational dimension of jobs, we examine the patterns and evolution of occupations in 22 European countries from 2005 to 2015. Instead of pervasive job polarisation, we observe a near-pervasive trend of upgrading job quality, suggesting that job polarisation may be caused by the undervaluation/devaluation of jobs low in the occupational hierarchy – not by computerisation-driven changes in work tasks. Indeed, only the former can explain the decrease in the number of low-quality jobs while the number of low-paid jobs increases. After documenting the relevance of firm-level organisational choices, we suggest that counteracting job polarisation requires, beyond meso-level collective bargaining, a public intervention that promotes participatory decision-making in firms.